Novel analogues of a nonnucleoside SARS-CoV-2 RdRp inhibitor as potential antivirotics - Tóth, Luca Julianna; Krejčová, Kateřina; Dejmek, Milan; Žilecká, Eva; Klepetářová, Blanka; Poštová Slavětínská, Lenka; Bouřa, Evžen; Nencka, Radim (Beilstein journal of organic chemistry, 2024)
The RNA-dependent RNA polymerase (RdRp) represents a prominent target in the discovery and development of new antivirotics against RNA viruses, inhibiting the replication process. One of the most targeted RNA viruses of the last years is, without doubt, SARS-CoV-2, the cause of the recent COVID-19 pandemic. HeE1-2Tyr, a known inhibitor of flaviviral RdRp, has been discovered to also have antiviral potency against this coronavirus. In this study, we report three distinct modifications of HeE1-2Tyr: conversion of the core from a benzothiazole to a benzoxazole moiety and two different scaffold simplifications, respectively. We provide a novel synthetic approach and, in addition, evaluate the final molecules in an in vitro polymerase assay for biological activity.
Keywords: antivirotics; RNA-dependent RNA polymerase; SARS-CoV-2; nonnucleotide inhibitor